Harmonizing lifelong learning with Islamic values: a framework for personal and societal development - Nordin, Ossman; Nik Abdullah, Nik Md. Saiful Azizi; Abdullah, Mohamad Ridhuan (Nungemilang Enterprise, 2024)
The paper "Harmonizing Lifelong Learning with Islamic Values: A Framework for Personal and Societal Development" explores the integration of lifelong learning with Islamic principles to address the challenges posed by modernity and digital globalization. It emphasizes the significance of grounding lifelong learning in Islamic ethics to foster spiritual, moral, and intellectual growth amidst technological advancements. The paper argues for a holistic approach to learning that transcends traditional education, promoting a culture of continuous knowledge acquisition, adaptability, and collaboration, aligned with Islamic teachings. It identifies key challenges such as the alignment of technology use with Islamic values, the need for inclusive and collaborative learning environments, and the imperative of continuous improvement in educational practices. Through a comprehensive literature review, the paper articulates how lifelong learning within an Islamic framework can contribute to personal enrichment and societal advancement, encouraging Muslims to engage with modernity while upholding their faith and values. This framework serves as a powerful mechanism for nurturing development rooted in faith, knowledge, and ethical conduct, offering insights into creating learning environments that reflect Islamic principles of justice, inclusivity, and excellence.